2014
DOI: 10.11138/mltj/2014.4.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Can arthroscopic revision surgery for shoulder instability be a fair option?

Abstract: SummaryBackground: the aim of this study was to evaluate the role of arthroscopic capsuloplasty in the treatment of failed primary arthroscopic treatment of glenohumeral instability. Methods: we retrospectively examined at a minimum of 3-years follow-up 22 patients who underwent arthroscopic treatment between 1999 and 2007 who had recurrent anterior shoulder instability with a post-surgical failure. A statistical analysis was performed to evaluate which variable could influence the definitive result and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In fact, some Authors showed that the Bankart arthroscopic procedure seems to be associated with a significant risk of recurrence in athletes: these failures appear to be due to the presence of bone loss 22 . The open surgery has a role only in the case of previous diseases and in case of recurrence after arthroscopy 23 . According to our observations, although the follow-up isn't long enough, the arthroscopic surgical approach appears to be excellent in shoulder instability management and it is therefore very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some Authors showed that the Bankart arthroscopic procedure seems to be associated with a significant risk of recurrence in athletes: these failures appear to be due to the presence of bone loss 22 . The open surgery has a role only in the case of previous diseases and in case of recurrence after arthroscopy 23 . According to our observations, although the follow-up isn't long enough, the arthroscopic surgical approach appears to be excellent in shoulder instability management and it is therefore very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is commonly used also in cases of failure of arthroscopic repair. When arthroscopic stabilization failing to increase stability of the shoulder a new arthroscopic approach in not raccomandable in all the cases, also in absence of great bone loss 21 . Patte described in 1980 stabilizing mechanism of Latarjet proponing the triple-blocking effect 2 ; Yamamoto later 22 in cadaveric study found that sling effect was the most important and bone effect much less.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a tendency to increase indications for arthroscopic treatment has been observed. 1 , 4 , 6 , 7 , 8 , 9 , 10 In the United States, between 2003 and 2005, 71.2% of all Bankart lesions were treated with arthroscopy, while between 2006 and 2008 this percentage increased to 87.7%. 2 The literature is controversial regarding which method achieves better results, especially when the prevalence of recurrence of dislocation after surgery is assessed.…”
Section: Introductionmentioning
confidence: 99%
“… 2 The literature is controversial regarding which method achieves better results, especially when the prevalence of recurrence of dislocation after surgery is assessed. 1 , 4 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation